Perfectionism and stress coping strategies in elite basketball - Rogaleva, L.; Dubinkina, Y.; Vichuzhanin, R.; Martynova, T. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to test and analyze the dominant aspects of perfectionism in a university elite basketball sample and their correlations with the key stress coping strategies.Methods and structure of the study. We sampled for the study the Ural Federal University basketball team leaders (n=11) aged 25 years on average. The sample was tested for the adaptive perfectionism / maladaptive perfectionism us-ing the FMPS (Frost, Marten, Lahart & Rosenblate, 1990) multidimensional perfectionism test scale. The stress coping strategies were profiled by the Coping strategies (Coping Strategies in Sports) test (ACSQ-1; Kim 1999; Kim & Duda, 1997). The test data were processed by a regression analysis in the standard mathematical statistics toolkit.Results and conclusion. The study found a direct correlation of maladaptive perfectionism with the Social Support Seeking stress coping strategy and an inverse correlation of the Doubts in Action with the Emotions Control stress coping strategy. Our tests and analysis of dominant aspects of perfectionism in the elite basketball sample and their correlations with the key stress coping strategies found dominance of adaptive perfectionism and constructive stress coping strategy. We also found that the higher are the doubts in own actions the lower is the individual emotional control in the stress coping strategies. The findings may be recommended for attention of sports psychologists, coaches and instructors